Site Response Characteristics of Simeulue Island, Indonesia as Inferred from H/V Spectral Ratio of Ambient Noise Records - Titi Anggono; Syuhada Syuhada; Nugroho Dwi Hananto; Lina Handayani (Institute for Research and Community Services (LPPM) ITB, 2016)
Simeulue Island is an outer island arc off west of the Sumatra Island. The Island is located close to the interface of the subduction zone between Indo-Australian and Eurasian Plates. Seismic activities around the Island included devastating megathrust earthquakes, such as 2004 MW 9.2 Sumatra-Andaman and 2005 MW 8.7 Nias earthquakes. We investigate the site response characteristics using Horizontal-to-Vertical (H/V) Spectral Ratio method to the continuous ambient noise records from eight broadband seismometers. From the calculation, we generally observe strong peak of H/V spectral ratio which is caused by the strong impedance contrast at these area. However, sites BATU, LABU and DEHI show relatively flat H/V spectral ratio curves that caused by lack of sharp impedance contrast beneath the site. We also observe multiple peaks at several sites that may indicate the presence of a more highly weathered soil/clay layer on top of a more compact medium. H/V peak frequencies, which shows fundamental frequencies resonance of soil sites, generally are observed at range about 2.0 - 16.4 Hz. From the observed H/V spectral ratio, we suggest that the strong impedance contrasts may occur on the shallow part of the medium at 2 up to15 m depth.